Skyrmion Dynamics in a Double-Disk Geometry Under an Electric Current: Part Two - Altbir-Drullinsky, D; Corona-Gonzalez, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Using numerical simulations, we studied the dynamics of two skyrmions nucleated in a double-disk structure. Depending on the geometry and the electric current, different regimes for the dynamical behavior of the skyrmions were obtained. Our results evidence that there are four main dynamic regimes depending on the geometry and current: stagnation points, oscillatory motion, and two types of skyrmion annihilation: partial and total. Our findings are explained as a result of the different forces that skyrmions are subject to and are shown in a state diagram of the dynamical states that allow an adequate understanding of the associate phenomena. © 2022 by the authors.